GC-MS analysis and in silico docking of constituents of Cinnamomum malabatrum against CYP450 17α and CYP450 19 (Aromatase)- Key targets for hyperandrogenism - Soumya, V.; Deepa, S.; Thachil, Knolin.K.; Saravanan, J.; Hariprasad, R. (Drug Research, 2023)
Poly cystic ovary syndrome (PCOS) is considered as one of the common hormonal disorders affecting 6–20% of women in their reproductive age with characteristic features include anovulatory infertility, hyperandrogenism, cystic follicles and insulin resistance. The gene CYP play an important role in pathophysiology of hyperandrogenism associated with PCOS. An elevated androgens are reported in PCOS condition due to overexpression of the enzyme CYP450 17 α. As well as diminished levels of aromatase (CYP450 19) were observed in several hyperandrogenic PCOS patients. The powdered leafy material of Cinnamomum malabatrum was subjected to Soxhlet extraction. The plant extract was subjected to Gas chromatography-MS analysis (GC-MS), and the chromatogram obtained revealed the presence of active chemical constituents like 1(10),9(11)-B-Homolanistadiene for the first time and other potential compounds. Hypothesis has raised to interpret the efficiency of phytoconstituents of Cinnamomum malabatrum on these enzyme targets and which may be a novel drug candidate for the treatment and maintenance of hyperandrogenism associated with PCOS. Thus, the results obtained from the in-silico study of Cinnamomum malabatrum leaf extract using computational approaches indicate that the phytoconstituents have good affinities for the selected two key targets. ADME and PASS studies has been performed for active phytoconstituents homolanistadiene, β-sitosterol, cycloartenol and a pyrazole derivative, and results revealed the Lipinski drug-likeness and pharmacological potential. In conclusion, this work throws a new insight into the possibility of the active phytoconstituents on binding the two active CYP45017 α and CYP45019 aromatase enzymes which facilitates development of novel compounds for hyperandrogenism associated with PCOS.
Keywords: PCOD; Cinnamomum malabatrum (N. Burm.) Bl; CYP450 17 α enzyme; CYP 450 19 aromatase; ADME; PASS